O mundo aos nossos olhos : socialização familiar e reflexividade - Caetano, Ana (Sociologia: Revista da Faculdade de Letras da Universidade do Porto, 2016)
The main goal of this article is to analyse the centrality of family socialisation processes in the formation of personal reflexivity, using a biographical approach. A diachronic overview on individual lives is crucial to understand not only how the ability to think about oneself is developed throughout the life course and is structured in a significant way within the family, but also how the impact of family socialisation in the formation of personal reflexivity competences occurs differently according to the family’s social background.